Form-focused grammar instruction effects on grammar accuracy and oral and writing proficiency in English - Oandasan, Richard L.
An important aspect of a language class is the teaching of grammar. Based on the assumption that language is a structured knowledge system, one of the main goals of second language learners is to develop awareness of the structure of language (Bialystok, 1989). To achieve this goal, there has been a paradigm shift from form-focused to meaning-focused type of instruction over the years. However, in the recent years through a number of research, some researchers have explored the effectiveness of switching back to form-focused grammar instruction (FFGI) to develop proficiency in a language. Motivated by this “pendulum-shift” to pedagogical grammar, the researcher investigated the effectiveness of FFGI and its relationship to two macro skills in language development, speaking and writing. This study aimed to explore the effects of FFGI on grammar accuracy, oral and writing proficiency. It also aimed to establish the correlation between oral and writing proficiency after the participants had undergone FFGI. The study adopted a one-group pretest-posttest design. A short autobiography, as a pre-test for oral proficiency and the Purdue online writing test for writing proficiency were administered among 31 participants who were enrolled in an English grammar class. To determine the scores for both tests, an oral proficiency rating scale and Lee and Paulson’s evaluation for composition were used. After the pre-test, the participants received form-focused grammar instruction. At the end of the term, the same tests were administered to determine whether or not improvements would be noted. To ensure objectivity and data integrity, the researcher sought the assistance of three professors in English to rate the tests. The findings revealed that there was no significant relationship between grammar accuracy and oral and writing proficiency. Likewise, there was no correlation between oral and writing proficiency after the participants had undergone form-focused grammar instruction (FFGI). Nonetheless, there was a significant difference in the participants’ pre- and post-test scores in the grammar accuracy test. The grammar post-test results were better compared to the pre-test scores. Based on the findings obtained from this study, it could be concluded that FFGI contributes to the improvement of grammar accuracy of students. The explicit discussion of grammar rules and target structure, drills, repetitions and error correction can aid in learning a language as also noted by Sheen (2003). Second, knowledge of grammar rules does not automatically result in oral and writing proficiency. While it is true that the study participants improved in their grammar accuracy after going through FFGI, they were not able to perfectly apply the correct language forms as shown by the incorrect grammar structures in their oral and written outputs. However, the results regarding the relationship between the participants’ grammar accuracy and writing and oral proficiency as well as the correlation between students’ oral and writing proficiency in English after being exposed to FFGI cannot be fully “generalizable” because of sample size constraints and other factors affecting language learning such as second language proficiency level, structure complexity, learning styles, and affective filter of the study participants. To further determine the effectiveness of FFGI as a methodology in developing language proficiency, future researchers can replicate the study by involving more participants for the results to be conclusive, extending the study for a longer period to establish the effect of sustained FFGI, and considering the factors previously cited.